2. Evaluation of Halal Slaughter-Man And Human Resource Competency In Slaughterhouse Category II - Zikri Maulina Gaznur; Henny Nuraini; Rudy Priyanto (Universitas Syiah Kuala, 2020)
This study was conducted to evaluate the performance level of halal slaughter in slaughterhouse category II as center of excellent. The study was performed in October 2015 to February 2016. The evaluation of halal slaughter-man competency and human resources competencies were conducted by observation form according to Indonesian Competency Standard (SKKNI) No 196/2014 and Indonesian Republic’s Regulation of Health Ministry No 13/OT.140/2010 regarding Slaughterhouse rules and Meat Cutting Plant Unit. Data obtained was analyzed descriptively. The result of Halal slaughter-man competency had met the Indonesian Competency Standard (SKKNI) and human resources competencies also were around the Regulation of Agriculture Ministry No. 13/2010.